Theatre, margins and politics an introduction - Ray, Arnab; Chakraborty, Sibendu (New Delhi : Routledge India, 2022)
This book interrogates the relationship of theatre and the dialectics of centre and the margins. It looks into the exciting world of performance to examine how theatre as an art form is perfectly placed to both perform and critique complex relations of power, politics, and culture. The volume looks into how drama has historically served as a stage for expressing and showcasing prevalent social, historical, and cultural contexts from which it has emerged or intends to critique. Including a wide range of performative practices like Dalit Theatre, Australian Aboriginal theatre, Western realism, and Yoruba theatre, it explores varied lived experiences of people, and voices of subversion, subalternity, resistance, and transformation. The book scrutinises the strategies of representation enunciated through textuality, theatricality, and performance in these works and the politics they are inextricably linked with. This book will be of interest and use to scholars, researchers, and students of theatre and performance studies, postcolonial studies, race and inequality studies, gender studies, and culture studies.
Keywords: Theater -- Cross-cultural studies; PERFORMING ARTS / Theater / General; SOCIAL SCIENCE / General